Clinical Evidence of Vestibular Dysregulation in Colicky Babies Before and After Chiropractic Treatment vs. Non-colicky Babies - Hoeve, Jan (Frontiers in Pediatrics, 2021)
Background: To date, after 66 years of research that was primarily directed at differentiating between normal and colicky crying, the cause of infantile colic remains elusive and no definitive cure has been found. Given the general absence of pathology, colicky crying is widely considered the extreme end of a spectrum of normal crying behavior. However, commonly associated symptoms suggest that infantile colic could reflect physiological dysregulation at the brainstem level, particularly of the vestibular and autonomic systems. The purpose of this study is to present a five-point clinical index of vestibular (hyper)activity and its application to investigate vestibular dysregulation in colicky and non-colicky babies. Methods: 120 consecutive colicky babies were evaluated using this index, before and after a very gentle vibratory treatment, and compared to 117 non-colicky babies. Results: Before treatment, of 120 colicky babies only 2 (1.7%) scored 0, whereas 118 (98.3%) scored scored 1-5. Of 117 non-colicky babies 89 (76,1%) scored 0 and 28 (23.9%) scored 1-3, none scored 4-5. The odds ratio is OR (CI 95%) 187.54 (43.52-808.09). After treatment 111 (92.5%) scored 0 and 9 (7.5%) scored 1-3, none scored 4-5. A McNemar test showed the difference before and after to be significant (χ² = 109.00, p < .001). For colicky babies the mean vestibular score is 2.88(SD 1.22), compared to 0.37(SD 0.73) for non-colicky babies, a difference of 87.2%. After treatment the score decreased from 2.88 (SD 1.12) to 0.10 (SD 0.40), or 96.5%. Conclusion: Colicky babies are not just infants who cry a lot. They also show clinical evidence of vestibular dysregulation. Treatment aimed at relaxing tight sub-occipital musculature by means of gentle vibrational stimulation may be effective in decreasing vestibular hyperactivity, signifying an improvement in brainstem regulation. The vestibular index opens the prospect for development into a tool towards an objective and practical clinical diagnosis of infantile colic.